Factors associated with time until metastatic spread in patients with primary uveal melanoma: A retrospective analysis - Reinhard Told; Adrian Reumueller; Judith Kreminger; Stefan Sacu; Roman Dunavoelgyi (PLoS ONE, 2025)
Purpose To characterize patients with choroidal or ciliary body (CB) melanoma in order to identify factors associated with time until metastasis and further perform a detailed characterization of the factors identified. Methods A mixed model approach was used to identify parameters and patient characteristics associated with time until metastatic event. Consequently, the identified parameters were characterized. Results In 383 patients with primary choroidal and CB melanoma, tumor thickness and patient age at diagnosis are associated with time until metastatic event. Mean patient age was 61 ± 13 years, mean choroidal and CB melanoma thickness was 5.1 ± 1.9 mm. Other factors investigated comprising sex, primary tumor width, length, volume, shape, and type of therapy are not associated with time until metastatic event in this patient collective. Conclusion In conclusion, this study expands the current knowledge on factors associated with metastasis due to primary choroidal or CB melanoma. So far primary choroidal or CB melanoma thickness has been shown to be a risk indicator for metastatic events. Now, we could show that primary choroidal or CB melanoma thickness is also correlated with time until metastatic event. The association can be expressed as: the thicker the primary tumor, the earlier the potential metastatic event. Age may be considered an indirect effect in the model calculated.